Inefficiency Of Ames Tester Strains To Detect Sodium (Meta) Arsenite As A Mutagen - P.V.SURESH REDDY,; K . HEMA KUMAR,; B. SRINIVASA RAO,; CH.V.SATISH KUMAR,; DR. G. R. DESHMUKH,; DR. LOKANATHA VALLURU, (International Journal of Pharma and Bio Sciences, 2012)
Arsenic is a well-known toxic and carcinogenic metalloid distributed all over the world causing serious health threats via drinking water. The present study was performed to evaluate the mutagenic potential of Sodium(meta)arsenite in the Bacterial Reverse Mutation Assay using five tester strains of Salmonella typhimurium TA1537, TA1535, TA98, TA100 and TA102. Sodium(meta)arsenite was not detected as mutagen in any of the tester strain, as it may act through other, non-genotoxic mechanism or mechanisms absent in bacterial cells.